Polybenzimidazoles based on 3,3 `-diaminobenzidine and aliphatic dicarboxylic acids: synthesis and evaluation of physicochemical properties toward their applicability as proton exchange and gas separation membrane material - Bhavsar, Rupesh S.; Nahire, Sandip B.; Kale, Mrunali S.; Patil, Shubhangi G.; Aher, Pradnya P.; Bhavsar, Ritesh A.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2011)
A series of aromatic-aliphatic polybenzimidazoles (PBIs) based on 3,3'-diaminobenzidine (DAB) and aliphatic dicarboxylic acid with incremental -CH2- groups were synthesized. Optimization of synthesis parameters and evaluation of physicochemical properties are requisite for PBI applicability as the proton exchange membrane (PEM) and gas separation membrane materials are reported. It was found that though all these PBIs exhibited high thermal, mechanical, and oxidative stability, effect of added flexibility on physical properties is not monotonous. Membranes were prepared by solution casting as well as phase-inversion method. The later types of membranes exhibited much higher H3PO4 content than its doping achieved in the solution casted membranes. These PBIs possess low hydrogen and helium permeability than that of conventional PBI. This low permeability, along with their excellent oxidative stability indicated that they can be promising PEM materials. Their CO2-sorption analysis revealed that PBI6 based on suberic acid possesses appreciable CO2 sorption. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 1090-1099, 2011
Keywords: Gas permeation; mechanical properties; membranes; oxidative stability; polybenzimidazoles

Polymeric ionic liquids (PILs): effect of anion variation on their CO2 sorption - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2012)
A series of polymeric ionic liquids (PILs) based on poly(diallyldimethylammonium chloride), P[DADMA][Cl] as a precursor was investigated by varying anions categorized into carboxylates, sulphonates and inorganic type. For the exchange of chloride from P[DADMA][Cl] by another anion, silver salt of the corresponding anion was preferred. Obtained PILs were investigated for physical properties which are anticipated to affect gas sorption. PILs possessing carboxylate (especially acetate) anion exhibited attractive CO2 sorption capacity as well as sorption selectivity over H-2 and N-2, in Comparison to Other two Categories. PIL with acetate anion, P[DADMA][Ac] possessed appreciable CO2 sorption coupled with high selectivity (S-CO2/S-N2 = 114.3). This crucial finding from this series of PILs was further substantiated by making PIL based on poly(vinylbenzyltrimethylammonium chloride), P[VBTMA][Cl] as a precursor. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; CO2 sorption; Polymeric ionic liquid

Film forming polymeric ionic liquids (PILs) based on polybenzimidazoles for CO2 separation - Kumbharkar, Santosh C.; Bhavsar, Rupesh S.; Kharul, Ulhas K. (RSC Advances, 2014)
PILs are emerging as promising materials for CO2 capture. Film formation, which is a requisite for membrane formation, is induced in a family of PILs by N-substituting a rigid thermo-mechanically stable polybenzimidazole, followed by metathesis. This provided two IL groups per repeat unit of the PIL and enhanced the CO2 separation characteristics.

Investigation of gas permeation properties of film forming polymeric ionic liquids (PILs) based on polybenzimidazoles - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2014)
Polymeric ionic liquids (PILs) are emerging as new generation membrane materials for CO2 separation. Gas permeation properties of a recently developed PIL family based on three structurally different polybenzimidazoles (PBIs) possessing excellent film forming characteristics are reported. Effects of cationic backbone and anions on gas permeation properties of PILs using pure gases (He, H-2, N-2, CH4, and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. In comparison to the parent PBIs, PILs exhibited generally higher CO2 permeability, without largely affecting CO2 based selectivity. Some of these PILs exhibiting high PCO2/PCH4, selectivity and P-H2/P-CO2, approaching similar to 1 indicated dominance of CO2 sorption over diffusion. The CO2 sorption specificity of these PILs was distinctly observed based on their improved S-CO2/S-N2, S-CO2/S-CH4 and S-CO2/S-H2 selectivity than their parent PBIs. A large variation in permeation properties of PILs based on a common polycation but different anions indicated that anions play a crucial role on governing gas permeation properties of these PILs. (C) 2014 Elsevier B.V. All rights reserved
Keywords: Gas permeation; Membranes for CO2 separation; Polybenzimidazole; Polymeric ionic liquid

Polybenzimidazole based film forming polymeric ionic liquids: synthesis and effects of cation-anion variation on their physical properties - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Rewar, Anita S.; Kharul, Ulhas K. (Polymer Chemistry, 2014)
Polymeric ionic liquids (PILs) are gaining wide attention due to their tunable properties and applicability in various upcoming areas, including membranes for CO2 separation. The known methodologies yield PILs that are difficult to convert into film form. The present work investigates a synthetic approach for obtaining PILs based on a strong film forming with a fully aromatic rigid backbone while incorporating ionic liquid character in it. Three structurally different polybenzimidazoles (PBI-I, PBI-BuI and ABPBI) were N-quaternized by a methyl group, followed by iodide exchange with various promising anions. The extent of iodide exchange by another anion was high enough (>94% in most cases). Most of the resulting PILs with various anions offer mechanically strong films, with the exception of those based on acetate and benzoate as an anion. Although the base PBI has excellent film forming ability, this result conveyed the role of anion in governing the film forming ability of the PIL. Salient features of this methodology include a fully aromatic polycation backbone, wide structural tunability (by virtue of variation not only of the anion/cation, but also with N-substituent) and introducing two IL characters per repeat unit of a PIL (except for PILs based on ABPBI). Attempted PIL structural variations showed diverse property variations in bulk and surface properties (solvent solubility, contact angle, water sorption, thermal stability, polyelectrolyte behaviour, CO2 sorption and ionic conductivity). Mechanical properties of film forming PILs exhibited high enough tensile strength, conveying their applicability as membrane materials.

Polybenzimidazole based polymeric ionic liquids (PILs): effects of controlled degree of N-quaternization on physical and gas permeation properties - Rewar, Anita S.; Bhavsar, Rupesh S.; Sreekumar, K.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric ionic liquids (PILs) are gaining increasing attention as potential membrane materials to be employed for CO2 separation. With a goal to improve gas permeability, this work presents a series of film forming PlLs obtained by controlled degree of N-quaternization (DQ) of PBI-BuI using a bulky 4-tertbutylbenzyl group. Concurrent effects of variation in ionic content and bulky group substitution were analyzed for physical and gas permeation properties of the resulting PILs. Attempted structural variations leading to simultaneous increments in ionic content and bulky groups offered amorphous polymers with acceptable thermal stability and non-monotonous chain packing density. Enhancement in pure gas permeability coupled with appreciable selectivity for various gas pairs was in accordance with the packing density variations in the series. Gas permeability showed maxima at DQ of just 13%. This conveyed that effects of bulky group substitution in retarding chain packing are overcome by attractive ionic interactions at much lower DQ in these PILs ionic interactions are thus more predominant in governing chain packing and gas permeation properties. These PILs possessed 3.3-20 times higher CO2 permeability in comparison to their parent PBI-BuI, without a significant loss in selectivity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Degree of quaternization; Gas permeation; Polybenzimidazole; Polymeric ionic liquid

Characterizing the nanoclay induced constrained amorphous region in model segmented polyurethane-urea/clay nanocomposites and its implications on gas barrier properties - Rath, Sangram K.; Sudarshan, Kathi; Bhavsar, Rupesh S.; Kharul, Ulhas K.; Pujari, Pradeep K.; Patri, Manoranjan; Khakhar, Devang V. (Physical Chemistry Chemical Physics, 2016)
There has been an increasing recognition of the fact that purely geometric factors associated with clay platelet dispersion in a polymer matrix cannot adequately explain the barrier properties of polymer/clay nanocomposites. The objective of the present work is to understand the nanoclay induced structural changes in a polyurethane-urea matrix and clay dispersion at different length scales using segment-specific characterization techniques and implications of the same in gas barrier properties using He, N-2 and CO2 as probe molecules. Wide angle X-ray diffraction (WAXD) and positron annihilation life time spectroscopy (PALS) studies revealed nanoclay induced alterations in the chain packing of the amorphous soft segments of the polyurethane matrix at a molecular scale of a few Angstroms. The hard segment organization and the phase morphology of the nanocomposites, spanning length scales of several nanometers, were investigated by small angle X-ray scattering (SAXS), scanning electron microscopy (SEM) and atomic force microscopy (AFM). Furthermore, the presence of a constrained amorphous region surrounding the nanoclay was confirmed from AFM, WAXD and PALS results. Several pertinent structural variables from the gas transport point of view were deduced from these characterization techniques to understand the effect of the barrier properties in tandem with the clay dispersion morphology.